Factors influencing purchase of foreign goods by Malay Muslim consumers: a structural equation modelling approach on religiosity and ethnocentrism perspectives - Haque, A. K. M. Ahasanul; Rahman, Sabbir; Ahmed, Ismail Sayyed (Medwell Publishing, 2011)
The purpose of this research was to study the relationship between religiosity and consumers ethnocentrism towards the purchase of foreign goods by the Malay Muslim Consumers. This study also highlighted some propositions to guide future empirical research. Total of 450 questionnaires was distributed for measuring the relationship between religiosity and ethnocentrism towards the purchase behaviour of Malay Muslim consumers in Klang Valley area. Finally, 300 questionnaires was validated and tested for further statistical analysis through exploratory factor analysis (EFA) and later confirmatory factor analysis (CFA). In addition,structural equation modelling technique (SEM) was applied for testing the hypotheses. Among all the important variables, consumer’s religiosity behaviour played most significant role followed by ethnocentrism attitude in buying foreign products. The results suggested that a significant proportion of Malay Muslim consumers were interested in country-of-origin information before making a purchase decision of foreign goods. This paper is added value between theory and practice, to explore religiosity and ethnocentrism behaviour on Malay Muslim consumer’s to purchase foreign products. Moreover, this is a relatively new issue that remains largely undiscovered by researchers under the perspective of Malay Muslim consumers’. This paper will also help to emphasize its importance and implications to business decisions.